The Global Finical Crisis from an Islamic Point Of View - Hewa Majeed Zangana (Qubahan Academic Journal)
When the world economy suffered a new financial economic crisis, it uncovered to the world that there were major failures within the Industrial financial system and it was caused by a number of issues including the practice of interest and the terrible effect it has on the financial crisis events. Issues that will be discussed in this paper are Riba, Gambling, Uncertainty, Derivatives, Saucerization, Sell of debt, Creation of Money, and the Private “Personal” interests. However, the paper will focus on the Islamic financial system and the financial instruments which are based and designed in compliance with Shariah Rules and Regulations, whether if practicing Islamic banking would cause such a crisis to accrue.